Percolation of two-dimensional multiwall carbon nanotube networks - Lee, Heon Sang; Yun, Chang Hun; Kim, Sun Kug; Choi, Ji Hoon; Lee, Cheol Jin; Jin, Hyoung-Joon; Lee, Hyunjung; Park, Sang Joon; Park, Min (AMER INST PHYSICS, 2009)
We highlight the significance of multiwall carbon nanotube (MWCNT) shape on the electrical percolation. For rodlike MWCNTs, percolation threshold depends on aspect ratio (L/d). For random coil-like MWCNTs, the percolation threshold does not depend on L/d but depends on the shape factor of MWCNTs represented by the ratio between static bending persistence length and diameter. Surface resistivities of various MWCNTs converge into single curve when we plot their dimensionless surface concentration versus surface resistivity. The surface resistivity of MWCNT films decrease with increasing temperature, particularly at low concentrations, indicating the films can be used as a negative temperature coefficient thermistor. (C) 2009 American Institute of Physics. [doi: 10.1063/1.3238326]
Keywords: ELECTRICAL-CONDUCTIVITY; TRANSPARENT; COMPOSITES; FILMS